National family health survey: some thoughts - Kanitkar, Tara (1999)
For the first time by achieving a degree of uniformity in the administering of questionnaires, sampling methods, data collection, analysis and presentation, the NFHS has been able to generate data on demographic characteristics which are comparable across regions. - Reproduced
Keywords: Surveys; Health services - India; Health services